Lessons Learned on the Tensile and Bond Behavior of Fabric Reinforced Cementitious Matrix (FRCM) Composites - de Felice, Gianmarco; D'Antino, Tommaso; De Santis, Stefano; Meriggi, Pietro; Roscini, Francesca (Frontiers in Built Environment, 2020)
Fabric Reinforced Cementitious Matrix (FRCM) composites represent an effective, compatible and cost-efficient solution for strengthening and retrofitting existing structures. A strong research effort was done to investigate the tensile and bond properties of these materials, as well as the overall behaviour of strengthened members. A Round Robin Test was organized by Rilem TC 250-CSM on 28 FRCM composites comprising basalt, carbon, glass, PBO, aramid and steel textiles, embedded in either cement, lime or geopolymer mortars, to collect an experimental dataset and define test protocols. This paper collects the outcomes of this study to highlight fundamental properties of FRCM and to investigate the variability of test results. Grid spacing, equivalent thickness of the textiles and mechanical properties of FRCM composites, such as stiffness, tensile and bond strength, are provided. Based on the comparison of experimental outcomes, the scatter of the mechanical properties is estimated, as a consequence of the quasi-brittle behaviour of the inorganic matrix and its sensitivity to manufacturing, curing and handling processes. Eventually, the influence of testing implementation, such as gripping method and measuring techniques, are outlined.